PEMBUATAN HOMEMADE BITTERS BERBAHAN BAKU LOKAL DENGAN METODE SOUS VIDE - Aldio Alif Dahmara Putra; Ridwan Iskandar (Eduturisma, 2019)
This experimental study aims to determine the making of homemade bitters made from local raw materials, namely secang wood, cardamom and galangal with base spirit is vodka with the sous vide method. The research method used is an experimental research method. The study population was 30 people who were accustomed to consuming or buying bitter drinks in several bars in Jakarta and Bandung. The method of data collection is done by distributing questionnaires to the panelists. Data analysis methods were used, namely organoleptic test, Variant Analysis (ANOVA) and t test, Tukey Ba, with the help of Microsoft Excel 2010 and SPSS.22 software (Statistical Product for Service Solution). The results of the study were obtained, homemade bitters with a composition of 300ml vodka, 40gr secang wood, 20gr cardamom and 40 gr galangal which were received by all panelists in terms of taste, aroma, color and taste left behind (aftertaste). Laboratory test results on homemade bitters show an alcohol content of 20.64%.